Investigação de possíveis mecanismos de ação ansiolítico, antidepressivo e analgésico do carvacrol em camundongos : estudos comportamentais, neuroquímicos e participação do estresse oxidativo - Melo, Francisca Helvira Cavalcante (2014)
Carvacrol (5-Isopropyl-2-methylphenol) is a monoterpenic phenol present in the essencial oil of many plants. It is the major component of the essential oil fraction of oregano and thyme. Knowing the antidepressant and anxiolytic actions of carvacrol, this work presents an analysis of monoamines and amino acids concentrations in mice striatum after oral treatment with carvacrol at doses of 25 and 50 mg / Kg. The results showed increased expression of dopamine in both doses of carvacrol and increased levels of GABA, aspartate, glycine and taurine at the dose of 25 mg / kg. Knowing the important role of oxidative stress in the pathophysiology of depression, the present work studied the effects of carvacrol at doses of 25 and 50 mg/Kg in animals submitted to previous injection of pilocarpine. The brain areas of hippocampus, striatum and prefrontal cortex were removed for analysis of MDA, nitrite-nitrate, catalase, SOD and GSH concentrations. The results showed that there was a decrease in MDA levels in both doses in all the studied brain areas. Nitrite and nitrate levels decreased in the striatum and hippocampus of animals treated with the dose of 50 mg/Kg and the animals treated with 25 mg/Kg showed a decrease in nitrite and nitrate levels in the hippocampus. The concentration of catalase at both doses decreased in the hippocampus and the levels of GSH increased in the dose of 50 mg/Kg in mice striatum and hippocampus. The SOD levels did not change. Since many antidepressant substances also have analgesic action, this work presented a study of the behavioral actions of carvacrol in animal models of nociception such as the formalin test, hot plate and acetic acid-induced abdominal constriction test. For these tests we used carvacrol at doses of 50 and 100 mg/Kg. In acetic acid induced-abdominal constriction test, carvacrol at both doses reduced the number of writhes. In the hot plate test, carvacrol at both doses showed an increase in pain latency at the time of 60 min. In the formalin test, animals treated with carvacrol at a dose of 50 mg/Kg showed a decrease in paw licking time in the first phase of the test. The animals treated with carvacrol at a dose of 100 mg/Kg showed a reduction in paw licking time in both first and second phases of the test. Pretreatment with naloxone or L-arginine was unable to reverse the antinociceptive effect of carvacrol at a dose of 100 mg/Kg in acetic acid induced-abdominal constriction test. In the formalin test, pretreatment of mice with naloxone or L-arginine was also unable to reverse carvacrol antinociceptive effect at a dose of 100 mg/Kg in the first and second phases of the test. The open field and rota rod tests were performed at dose of 100 mg/Kg and showed no significant changes, demonstrating that the substance did not changed locomotor activity in mice. Acute toxicological evaluation was performed in mice pretreated with carvacrol at doses of 300 and 2000 mg/Kg. Histological analysis of liver, kidney and brain showed no change in these organs after treatment with carvacro.